2020
DOI: 10.1155/2020/8867140
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment Mechanism of the Upper Carboniferous-Lower Permian Transitional Shale in the East Margin of the Ordos Basin, China: Evidence from Geochemical Proxies

Abstract: The organic-rich shale of the Upper Carboniferous-Lower Permian transition period in the eastern margin of the Ordos Basin, China, was formed in a marine-continental facies sedimentary environment. With a high content of total organic carbon (TOC) and a large cumulative thickness, it is considered a good source rock for shale gas development. The sedimentary environment of marine-continental transitional shale is obviously different from that of marine shale, which leads to different enrichment characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The current research focuses on transitional shale gas, mainly focusing on the reservoir characteristics of the Shanxi Formation [11][12][13][14][15][16]. Systematic comparative studies of the Shanxi Formation and Taiyuan Formation are mostly performed with respect to sedimentary evolution, organic matter enrichment, and pore size distribution [17][18][19][20][21][22][23]. Specific research on the Taiyuan Formation has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The current research focuses on transitional shale gas, mainly focusing on the reservoir characteristics of the Shanxi Formation [11][12][13][14][15][16]. Systematic comparative studies of the Shanxi Formation and Taiyuan Formation are mostly performed with respect to sedimentary evolution, organic matter enrichment, and pore size distribution [17][18][19][20][21][22][23]. Specific research on the Taiyuan Formation has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The continental basins in China are widely distributed, and the continental shale is developed in many strata such as Mesozoic-Cenozoic [8][9][10][11], which is one of the required replacement fields for shale gas exploration. Industrial discoveries of continental shale gas are found in several Triassic stratigraphic wells in Ordos Basin and Jurassic strata in Sichuan Basin [12,13]. However, compared with marine shale, the output of continental shale gas is lower.…”
Section: Introductionmentioning
confidence: 99%